School Based Management in Improving the Quality of Elementary Schools - Fikriyah Fikriyah; Fidya Arie Pratama; Barnawi Barnawi; Afifah Mumtazah (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2024)
School-Based Management (SBM) is a decentralized approach to school management that provides greater autonomy to schools to improve the quality of education. This study aims to analyze the implementation of SBM in improving the quality of elementary schools. Using qualitative methods, data were collected through observation, interviews, and documentation studies in several elementary schools. The results of the study indicate that the implementation of SBM has a positive impact on improving the quality of education. Schools that implement SBM are able to develop curricula according to local needs, increase community participation, and optimize the use of resources. Principals, teachers, and school committees have strategic roles in decision-making and school management, thus creating a more conducive and effective learning environment. However, the success of SBM is also influenced by factors such as the competence of the principal, cooperation between school residents, and support from the government and community. This study recommends increasing training for principals and teachers and increasing community involvement in the education process as important steps to optimize the implementation of SBM. Thus, SBM can be an effective strategy to improve the quality of elementary schools in a sustainable manner